2015
DOI: 10.1097/mbc.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban and apixaban in orthopaedics

Abstract: The aim of this study was to improve knowledge of what happens in the coagulation of orthopaedic patients under rivaroxaban and apixaban, in order to finalize and cross-validate effective measurement methods and to provide arguments for helping to reference one or the other drug in our central pharmacy. One hundred and two patients undergoing total hip or knee replacement were included. Half of them received rivaroxaban and the other half received apixaban. Blood samples (n = 244 with each drug) were taken at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Mean apixaban concentration at our study at the peak level varied by eightfold, and rivaroxaban only by 1.5-fold, while in the phase III studies, a fourfold peak for apixaban and a 40-fold peak for rivaroxaban were observed. Our findings in orthopaedic patient population confirm the previous comparison of apixaban and rivaroxaban [19]; both markedly affected thrombin-generation variables in vitro, while F1 + 2 were stable in vivo. As ETP and peak correlated, and are both known to associate with VTE [20], we decided to focus on the ETP results.…”
Section: Discussionsupporting
confidence: 90%
“…Mean apixaban concentration at our study at the peak level varied by eightfold, and rivaroxaban only by 1.5-fold, while in the phase III studies, a fourfold peak for apixaban and a 40-fold peak for rivaroxaban were observed. Our findings in orthopaedic patient population confirm the previous comparison of apixaban and rivaroxaban [19]; both markedly affected thrombin-generation variables in vitro, while F1 + 2 were stable in vivo. As ETP and peak correlated, and are both known to associate with VTE [20], we decided to focus on the ETP results.…”
Section: Discussionsupporting
confidence: 90%
“…However, a qualitative assessment PT; aPPT; thromboelastography, and rotational thromboelastography) are not reliable for monitoring rivaroxaban, apixaban, edoxaban due to the complexity of standardization related to the large number of reagent variants used and the variability of results among patients 1911 . This is also demonstrated by studies involving patients after orthopedic interventions 1914,1915 .…”
Section: Mehmetmentioning
confidence: 69%
“…Rivaroxaban and apixaban have different effects on the coagulometric measurements of patients after THA and TKA. Freyburger et al, found that rivaroxaban resulted in a higher increase of antithrombin levels, aPTT, PT and D-dimer compared to apixaban 1914 . Also, rivaroxaban more pronouncedly reduced the concentration of thrombin (thrombin generation test) than apixaban 1914,1916 .…”
Section: Mehmetmentioning
confidence: 99%
See 1 more Smart Citation
“…Their advantages are wide therapeutic index, fixed dose regimen, favorable efficacy/safety ratio, and minor drug−drug and drug−food interactions [6]. For example, apixaban is a selective inhibitor of blood clotting human factor-Xa [7,8]. It is also used to treat deep veins and pulmonary embolism and to prevent their recurrence [9].…”
Section: Introductionmentioning
confidence: 99%